Ethical Dynamics Through Asriadi's Educational Pantun in the Context of Daily Life: A Study of Self-Reflection - Esa Peggy Nerida Manurung; Rosmawaty Harahap (Winaya Inspirasi Nusantara Foundation, 2024)
Literature plays an important role in shaping people's thoughts, values, attitudes, and ethics in self-reflection. The purpose of this study is to analyze how ethical values transmitted through pantun affect the process of individual personality development, both psychologically, socially, and morally. This article analyzes the dynamics of ethics through Asriadi's educational pantun in the context of daily life, with an emphasis on self-reflection. This research uses a qualitative approach with a text analysis method. The analysis shows that the pantun contains moral messages relevant to ethics, such as self-introspection, humble attitude, personal responsibility, avoiding blame, and good self-awareness. This research has practical implications in increasing awareness and application of ethics in daily life.